PELATIHAN DESAIN KEMASAN & PEMOTRETAN PRODUK UNGGULAN KAMPOENG KAJOETANGAN HERITAGE KOTA MALANG - Bunyamin Bunyamin; St Munfaqiroh St Munfaqiroh; Dwi N A Dwi N A; Nunung N U Nunung N U; Kadarusman Kadarusman; Imama Z Imama Z; Setyawan Setyawan; Ali L Ali L; Triana M Triana M; Fera Tj Fera Tj; Sugeng H Sugeng H; Nanang P Nanang P (P3M Politeknik Negeri Malang, 2021)
The purpose of this training is to provide insight into new packaging designs and forms that make products more valuable while providing skills for basic product photo mastery so that they can make product photos that can showcase the advantages of their products.In this service, the methods used are lectures, discussions, and questions and answers about packaging design and product photography, training, starting with an introduction to the tools, materials, and media used as well as making product designs and photographing products, as well as by counseling and practice in packaging design and product photography.This activity is very useful in providing knowledge and practice in designing packaging and taking pictures of products as an effort to make consumers more interested in consuming the products of business actors in Kampoeng Kajoetangan, so that they are able to market their products online by displaying product photos that attract consumers to buy their products.